Population dynamics of lemon butterfly (Papilio demoleus) in bael (egle marmelos) as influenced by abiotic factors in (Indian Journal of Arid Horticulture, 2025)
It was observed that population and infestation of P. demoleus appeared from August to February. The highest egg, larval population and plant infestation were observed 12.75, 6.15/ 10 branches and 65.0%, respectively. The relationship between lemon butterfly egg, larval population and maximum temperature was (-0.53 & -0.55) negatively correlated whereas the maximum relative humidity was (0.44 & 0.53) positively correlated. Then, the egg and larval population gradually increased and reached to its peak, when the temperature decreased and humidity increased. The rainfall was also negatively correlated (-0.51) with egg population of lemon butter fly in arid region.
Keywords: Papilio demoleus; Aegle marmelos; population dynamics; abiotic